2013
DOI: 10.1371/journal.pone.0053252
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Non-Inferiority Study Comparing Efficacy and Safety of a Single Dose of Pegfilgrastim versus Daily Filgrastim in Pediatric Patients after Autologous Peripheral Blood Stem Cell Transplant

Abstract: PurposeTo assess the non-inferiority of pegfilgrastim versus filgrastim in speeding the recovery of polymorphonuclear cells (PMN) in pediatric patients who underwent autologous peripheral blood stem cell transplant (PBSCT).MethodsThe sample size of this randomized, multicenter, phase III study, was calculated assuming that a single dose of pegfilgrastim of 100 ug/kg was not inferior to 9 doses of filgrastim of 5 ug/kg/day. Randomization was performed by a computer-generated list and stored by sequentially numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…9 A number of small RCTs comparing pegfilgrastim and filgrastim have also been conducted in other patient populations, including pediatric patients 63,64 and adults who have undergone autologous SCT. 9 A comparison of pegfilgrastim and filgrastim was based on five clinical trials and suggested that pegfilgrastim was more effective than filgrastim at reducing the risk of febrile neutropenia (RR, 0.66; 95% CI, 0.44 to 0.98).…”
Section: Literature Review Update and Analysismentioning
confidence: 99%
“…9 A number of small RCTs comparing pegfilgrastim and filgrastim have also been conducted in other patient populations, including pediatric patients 63,64 and adults who have undergone autologous SCT. 9 A comparison of pegfilgrastim and filgrastim was based on five clinical trials and suggested that pegfilgrastim was more effective than filgrastim at reducing the risk of febrile neutropenia (RR, 0.66; 95% CI, 0.44 to 0.98).…”
Section: Literature Review Update and Analysismentioning
confidence: 99%
“…Filgrastim-associated sustained episodes of rigors with or without fever have not been reported in the literature. However, fever of unknown origin without rigors has been reported in a randomized clinical trial comparing safety and efficacy of single dose of pegfilgrastim versus daily filgrastim in pediatric patients undergoing autologus stem cell transplantation (Cesaro et al, 2013). Other studies of adult patients undergoing stem cell transplantation also report fever as one of the reversible adverse events associated with filgrastim administration (Orciuolo et al, 2011).…”
Section: Filgrastim-associated Fever and Rigorsmentioning
confidence: 99%
“…These factors all increase the risk of the recruitment, collection and reinfusion process of APBSC in children with solid tumors (14,15). The present study reports the outcomes of 38 children with advanced malignant solid tumors who received high-dose chemotherapy (HDCT) and APBSCT treatment between September 2005 and November 2011 in Beijing Tongren Hospital (Capital Medical University, Beijing, China).…”
Section: Introductionmentioning
confidence: 98%